PERFORMANCE ASSESSMENT IN SCIENCE NATIONAL LEVEL DIAGNOSTIC TESTS - Pestovs, Pāvels; Namsone, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
National Centre of Education of the Republic of Latvia in 2016 lunched national project of the renewal of the curriculum for education funded by the European Social Fund. One of the key priorities of successful implementation of the new education curriculum is transforming national level assessment system.Assessment system measuring student performance must meet different requirements from the traditional measurement instrument assessing content knowledge.Analysing 2017 national level science assessment diagnostic tests of 15-16 years old students, it is impossible to discriminate student different level of performance. Student, demonstrating singly stored pieces of knowledge, integrating pieces of knowledge into a coherent system, deriving general principle or transferring understanding to new situations, are assessed the same.The research goal is to analyse 9th grade student performance in national level science diagnostic testing, which measures conceptual understanding by explaining natural phenomena scientifically. This paper describes developing and calibrating measuring instrument assessing student performance according to the cycles of cognitive growth and taxonomy of observed learning outcomes.